2017
DOI: 10.1016/j.ecolind.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative criteria for choosing targets and indicators for sustainable use of ecosystems

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…Several holistic indicators are usable (Greenstreet and Rogers, 2006;Salas et al, 2006;Teixeira et al, 2016), including diversity measures, thermodynamicallyderived functions (Jørgensen and Mejer, 1979), tropho-dynamic indexes (Tudela et al, 2005), and others more or less specific for exploited marine ecosystems . Research actions are urgently needed to define those suites of indicators capable of establishing the appropriate reference levels to guide management strategies to recover the increasingly collapsed fish populations in our seas (Rossberg et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several holistic indicators are usable (Greenstreet and Rogers, 2006;Salas et al, 2006;Teixeira et al, 2016), including diversity measures, thermodynamicallyderived functions (Jørgensen and Mejer, 1979), tropho-dynamic indexes (Tudela et al, 2005), and others more or less specific for exploited marine ecosystems . Research actions are urgently needed to define those suites of indicators capable of establishing the appropriate reference levels to guide management strategies to recover the increasingly collapsed fish populations in our seas (Rossberg et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown how ecosystem modeling could support the assessment of different ecosystem components and pressures in several marine regions and also where models require further development (Hyder et al, 2015;Piroddi et al, 2015a;Tedesco et al, 2016;Rossberg et al, 2017). Here we advance on this body of work and demonstrating that modeling is not only useful for the assessment of components, but throughout the entire assessment cycle of the MSFD (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In general, we found SDT to be a robust and scientifically sound strategy for setting threshold values for indicators (Chuševė et al, 2016). Finally, we introduced a new approach to set indicator targets in relation to ecosystem resilience (i.e., the ability to recover rapidly and predictably from pressures) and to select indicators and their target ranges (Rossberg et al, 2017). This approach is a specific, quantitative interpretation of the concepts of GES and sustainable use in terms of indicators and associated targets.…”
Section: Development Of New Indicatorsmentioning
confidence: 99%